AB0409 An observational study of vitamin d in systemic lupus erythematosus patients: associations among vitamin d status, fatigue, quality of life and disease activity. (23rd January 2014) - Breslin, L. C.; Ball, E.; Armstrong, D.; Bell, A.; Magee, P.; Laird, E.; Wallace, J.; McSorley, E.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease in which fatigue and impaired quality of life (QoL) commonly manifest. Fatigue has been associated with increased disease activity in SLE 1 -3 and both fatigue and disease activity are considered predictors of impaired QoL 2 -4, although some studies have not reported any association between disease activity and QoL 5 -6 . Objectives: The aim of this study was twofold, firstly to determine whether vitamin D is associated with fatigue and QoL in SLE patients during the winter when status would be expected to be lowest and again during summer when vitamin D levels are thought to be highest and secondly to examine for any relationship between fatigue, QoL and disease activity. Methods: SLE patients were recruited from November to March (winter) (n=52) and followed up during June and July (summer) (n=50). Serum 25-hydroxyvitamin D (25(OH)D) was measured by liquid chromatography mass spectrometry. Fatigue was assessed using the fatigue severity score (FSS) and QoL was examined using the 36-item short form questionnaire (SF-36). Disease activity and damage were scored using versions of Systemic Lupus Activity Measure, Systemic Lupus Erythematosus Disease Activity Index, British Isles Lupus Assessment Group and Systemic Lupus International Collaborative Clinics/American College of Rheumatology. Primary statistical analysis included Spearman's rho correlation and two tailed paired t -test. Multivariate and logistic regression analysis was employed to investigate potential predictors of fatigue and QoL. To investigate whether vitamin D was associated with fatigue and QoL, data from the serial winter and summer measurements were combined to give a larger sample (n=102) with greater power and regression analysis was reapplied. Results: During the winter and summer months respectively 47 (96%) and 49 (98%) SLE patients reported fatigue (FSS ≥ 3) and 98% of the cohort presented with vitamin D inadequacy (25(OH)D < 75 nmol/L) throughout the year. The mental component score (MCS) (95% CI 0.02, 5.42, P =0.049) and social functioning (SF) (95% CI 1.01, 13.27 P =0.023) subscales of the SF-36 were reduced during the summer. Analysis from the serial winter and summer data, reported vitamin D status to be reduced in those with fatigue (n=96) (95% CI -39.46, -2.03, P =0.030) and FSS and SF-36 significantly correlated with all disease activity measures. Conclusions: Vitamin D inadequacy, fatigue and poor QoL were prevalent in this cohort of Northern Irish SLE patients. Given the observation of reduced vitamin D in those with fatigue and the association between vitamin D and disease activity, it is plausible that improvements in fatigue mediated via increasing 25(OH)D may indirectly improve disease activity and possibly enhance QoL. Further research such as placebo controlled vitamin D intervention trials are warranted to investigate this hypothesis before any firm conclusions can be made. References: Zonana-Nacach et al . Lupus 2000; 9(2):101-9. Kozora E et al . Arthritis Rheum 2006; 55(4):628-35. Mattsson et al. Scand J Rheumatol 2008; 37(4):269-77. Jolly & Utset. Lupus 2004; 13(12):924-6. Moldovan et al . Lupus 2011; 20(12):1285-92. Leong et al . Lupus 2010; 19(1):100-6. Disclosure of Interest: None Declared